LncRNA Dlx6os1 Accelerates Diabetic Nephropathy Progression by Epigenetically Repressing SOX6 via Recruiting EZH2 - Yan-Xia Chen; Shu-Ying Zhu; Chong Huang; Cheng-Yun Xu; Xiang-Dong Fang; Wei-Ping Tu (Karger Publishers, 2022)
Introduction: Diabetic nephropathy (DN) is the leading cause of kidney failure worldwide. To explore the pathogenesis and effective biological target of DN is beneficial to seeking novel treatment strategies. Objective: This study aimed to investigate the role of the lncRNA Dlx6os1/SOX6/EZH2 axis in DN progression. Methods: PAS staining was performed to evaluate extracellular matrix accumulation; ELISA was carried out to assess the levels of urine microalbumin and blood glucose concentration; RT-qPCR was carried out to detect the levels of lncRNA Dlx6os1, TNF-α, IL-1β, IL-6, SOX6, and EZH2. Western blot was performed to assess the levels of Col-IV, FN, TGF-β1, and SOX6 proteins. RIP assay was carried out to verify the interaction between lncRNA Dlx6os1 and EZH2. ChIP-qPCR was conducted to verify the interaction between EZH2 and SOX6 promoter. Results: Our results illustrated that lncRNA Dlx6os1 was highly expressed in DN mice and HG-induced SV40 MES13 cells. LncRNA Dlx6os1 knockdown inhibited HG-induced SV40 MES13 cell proliferation, fibrosis, and inflammatory cytokine release. LncRNA Dlx6os1 inhibited SOX6 expression by recruiting EZH2 in HG-SV40 MES13 cells, and SOX6 mediated the effects of lncRNA Dlx6os1 on proliferation, fibrosis, and inflammatory factor release of HG-induced SV40 MES13 cells. Conclusion: LncRNA Dlx6os1 accelerates the progression of DN by epigenetically repressing SOX6 via recruiting EZH2.